Elevated early lesion water uptake in acute stroke predicts poor outcome despite successful recanalization – When "tissue clock" and "time clock" are desynchronized. Issue 7 (October 2021) - Nawabi, Jawed; Flottmann, Fabian; Kemmling, Andre; Kniep, Helge; Leischner, Hannes; Sporns, Peter; Schön, Gerhard; Hanning, Uta; Thomalla, Götz; Fiehler, Jens; Broocks, Gabriel
Background: Ischemic water uptake in acute stroke is a reliable indicator of lesion age. Nevertheless, inter-individually varying edema progression has been observed and elevated water uptake has recently been described as predictor of malignant infarction. Aims: We hypothesized that early-elevated lesion water uptake indicates accelerated "tissue clock" desynchronized with "time clock" and therefore predicts poor clinical outcome despite successful recanalization. Methods: Acute middle cerebral artery stroke patients with multimodal admission-CT who received successful thrombectomy (TICI 2b/3) were analyzed. Net water uptake (NWU), a quantitative imaging biomarker of ischemic edema, was determined in admission-CT and tested as predictor of clinical outcome using modified Rankin Scale (mRS) after 90 days. A binary outcome was defined for mRS 0–4 and mRS 5–6. Results: Seventy-two patients were included. The mean NWU (SD) in patients with mRS 0–4 was lower compared to patients with mRS 5–6 (5.0% vs. 12.1%; p < 0.001) with similar time from symptom onset to imaging (2.6 h vs. 2.4 h; p = 0.7). Based on receiver operating curve analysis, NWU above 10% identified patients with very poor outcome with high discriminative power (AUC 0.85), followed by Alberta Stroke Program Early CT Score (ASPECTS) (AUC: 0.72) and National Institutes of Health Stroke Scale (NIHSS) (AUC: 0.72). Conclusions: Quantitative NWU may serve as an indicator of "tissue clock" and pronounced early brain edema with elevated NWU might suggest a desynchronized "tissue clock" with real "time clock" and therefore predict futile recanalization with poor clinical outcome.